A4NH 2013 annual report - CGIAR Research Program on Agriculture for Nutrition and Health; Keeton, Kimberly; Marble, Andrew; Whitehead, John; Block, Charlotte; Bouis, Howarth E.; de Brauw, Alan; Defabachew, Tigist; Gillespie, Stuart; Grace, Delia; Johnson, Nancy L.; McDermott, John; et al. (International Food Policy Research Institute, 2014)
In its second full year, the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) has progressed from establishing its research agenda and partnerships, to identifying and assessing key drivers of change, the role of different actors, and the potential for different approaches to catalyze change and improve the nutrition and health of poor communities.